The Role of Band Music Extracurricular Activities in Enhancing Students’ Musical Skills at SMA Negeri 1 Wonogiri - Bima Ramadhan; Bagus Susetyo (Jurnal Ragam Pengabdian, 2026)
Band music extracurricular activities at SMA Negeri 1 Wonogiri demonstrate the role of music education as a medium for developing students’ musical skills, creativity, and social attitudes within the school environment. The implementation of well-structured practice sessions, teacher guidance, and facility support encourages students to demonstrate competitive and high-achieving musical abilities, as reflected in accomplishments at the regional level. This condition affirms the function of band music extracurricular activities as a space for the actualization of artistic potential and the integrated development of student character. This study employs a descriptive qualitative approach to understand the role of band music extracurricular activities in enhancing students’ musical skills at SMA Negeri 1 Wonogiri. Data were collected through participatory observation, structured interviews, and documentation, and their validity was examined through technique and source triangulation. The findings indicate that band music extracurricular activities at SMA Negeri 1 Wonogiri play a significant role in improving students’ musical skills through systematic coaching, continuous practical training, integrated learning strategies, and adequate support of facilities and infrastructure. These activities foster technical mastery, musical understanding, ensemble performance skills, as well as social and character competencies in the form of cooperation, discipline, responsibility, and self-confidence, as evidenced by achievements in various music art competitions.